2017
DOI: 10.5296/ije.v9i4.12124
|View full text |Cite
|
Sign up to set email alerts
|

Impact of School Feeding Programme on Access to Basic Education: The Case of South Tongu District of the Volta Region, Ghana

Abstract: The study examined the impact of the school feeding programme on access to basic education in the South Tongu district in the Volta Region, Ghana. A convergent parallel mixed method research design was employed to conduct the study. Stratified random sampling and purposive sampling procedures were used to select 213 respondents for the study. Questionnaires, interviews and focus group discussion were used to collect the data for the study. Data gathered through questionnaires was analysed using descriptive sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…For Gyasi et al (2018), the quality of food given to beneficiary pupils improved their academic performance. This outcome was reinforced by the findings of Milledzi et al (2017) which revealed that the academic performance of pupils increased with the starting of the SFP. In support of this, one of the beneficiary pupils stated "…When I eat, I become alert and able to concentrate.…”
Section: Impact On Cognitive Outcomesmentioning
confidence: 82%
See 4 more Smart Citations
“…For Gyasi et al (2018), the quality of food given to beneficiary pupils improved their academic performance. This outcome was reinforced by the findings of Milledzi et al (2017) which revealed that the academic performance of pupils increased with the starting of the SFP. In support of this, one of the beneficiary pupils stated "…When I eat, I become alert and able to concentrate.…”
Section: Impact On Cognitive Outcomesmentioning
confidence: 82%
“…This behavioural change by parents and their children is manifested in the levels of increase in such results as enrolment, attendance and retention (Lawson, 2012). Among the 16 sample studies of this review, 13 reported the positive impact of GSFP on behavioural outcomes (Aliu and Fawzia, 2014;Gyasi et al, 2018;Konzabre, 2018;Kudus, 2011;Mahama, 2017;Milledzi et al, 2017;Nyarko, 2014;Odame, 2014;Oduro-Ofori and Adwoa-Yeboah, 2014;Osei-Fosu, 2011;Serebour, 2017;Tagoe, 2018;Yendaw and Dayour, 2015). School enrolment increases due to SFP have been reported in 13 studies while 12 studies each reported the positive impact of SFP on attendance and retention (Table 3).…”
Section: Impact On Behavioural Outcomesmentioning
confidence: 99%
See 3 more Smart Citations